4(3x+2)+29=15x+4-4x+33

Simple and best practice solution for 4(3x+2)+29=15x+4-4x+33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+2)+29=15x+4-4x+33 equation:


Simplifying
4(3x + 2) + 29 = 15x + 4 + -4x + 33

Reorder the terms:
4(2 + 3x) + 29 = 15x + 4 + -4x + 33
(2 * 4 + 3x * 4) + 29 = 15x + 4 + -4x + 33
(8 + 12x) + 29 = 15x + 4 + -4x + 33

Reorder the terms:
8 + 29 + 12x = 15x + 4 + -4x + 33

Combine like terms: 8 + 29 = 37
37 + 12x = 15x + 4 + -4x + 33

Reorder the terms:
37 + 12x = 4 + 33 + 15x + -4x

Combine like terms: 4 + 33 = 37
37 + 12x = 37 + 15x + -4x

Combine like terms: 15x + -4x = 11x
37 + 12x = 37 + 11x

Add '-37' to each side of the equation.
37 + -37 + 12x = 37 + -37 + 11x

Combine like terms: 37 + -37 = 0
0 + 12x = 37 + -37 + 11x
12x = 37 + -37 + 11x

Combine like terms: 37 + -37 = 0
12x = 0 + 11x
12x = 11x

Solving
12x = 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
12x + -11x = 11x + -11x

Combine like terms: 12x + -11x = 1x
1x = 11x + -11x

Combine like terms: 11x + -11x = 0
1x = 0

Divide each side by '1'.
x = 0

Simplifying
x = 0

See similar equations:

| 12=a/36+47 | | X+1+4x=1 | | 2(x-3)-4(x-2)=-2 | | 150m-75m+55,550=53.350-200m | | 11x+4=147 | | -6-4r=-4(r+2) | | 4.25x=36+3.50x | | 4.25x=36+3.50c | | 4.25x=36+3.50 | | 100-5c=10 | | -3y-10=4y-39 | | 150m-75m+53,350=55,550-200m | | 3(5-2x)+2x=15-4x | | 24n=-12-12 | | 19+0.55=95.30 | | 3x^2-6x+4=3 | | 2x+x+4=8x-5x+4 | | -24-x=6 | | n/n+12=9/12 | | -3a+6(7a-1)=189 | | 16y-12y=20 | | 6x+36=54 | | 3(x+4)=8x+7-5x+5 | | x^2+3y^2-6x+6y=0 | | 12x+4=13x+-5 | | e/12+25=29 | | 2.5(x+2)+4.5+15(x-3)=15 | | 6/4x+1/2=4/9-1/7x+4/9 | | 5.4+a=7.5 | | 8x-9y=96 | | 9x21/6 | | -66=-3+7n |

Equations solver categories